2019
DOI: 10.1016/j.sdentj.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of prevalence of apical periodontitis in smokers and non-smokers using cone-beam computed tomography

Abstract: ObjectiveThe aim of this study was to compare the prevalence and size of periapical lesions among smokers and non-smokers using cone-beam computed tomography (CBCT).Materials and methodsRetrievable CBCT datasets for 46 male patients ≥18 years during a consecutive period from 2008 to 2016 were examined. The medical, smoking history and other clinical findings (signs of previous dental trauma; Decayed Missing Filled Teeth (DMFT) scores; the percentage of root filled teeth; and oral hygiene status) were obtained.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
1
16
0
1
Order By: Relevance
“…A key feature in this research is counting samples as per tooth not per patient, our opinion matches (Balto et al 2019) as this would give a truer picture of the disease distribution and severity, if we put in mind that a patient with three or more affected teeth is not equal to a person with only one tooth affected with the condition in question which is AP. 37 The endodontic treatment itself is multifactorial too because it passes through instrumentation, irrigation, and lastly obturation, unfortunately, we cannot trace the first two procedures because its operator-dependent and undocumentable, so we depended on the quality of obturation obtained from OPG's and later from PA X-ray to judge the quality of RCT.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…A key feature in this research is counting samples as per tooth not per patient, our opinion matches (Balto et al 2019) as this would give a truer picture of the disease distribution and severity, if we put in mind that a patient with three or more affected teeth is not equal to a person with only one tooth affected with the condition in question which is AP. 37 The endodontic treatment itself is multifactorial too because it passes through instrumentation, irrigation, and lastly obturation, unfortunately, we cannot trace the first two procedures because its operator-dependent and undocumentable, so we depended on the quality of obturation obtained from OPG's and later from PA X-ray to judge the quality of RCT.…”
Section: Discussionmentioning
confidence: 69%
“…However, there are no data on this topic in the Iraqi population. regarding smoking negative role in AP, [33][34][35] alongside with other authors; knowing that smoking alters the microvasculature and the function of immune system, the cadmium that is found in cigarettes also consumes the Super Oxide dismutase protective enzyme which is an anti-oxidant-in blood and saliva, by replacing the Manganese, copper, and Zinc leaving SOD in an inactive state opening the door to the free radicals generated from smoking to destroy periodontal tissue 33 and this was obvious in the significant relationship between groups (G-c, Ge 6,36,37 suggesting that the development of AP in RCT teeth is multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that cigarette smoking has local and direct pro-inflammatory effect on inflamed periapical tissues, with increased levels of products of lipid peroxidation, such as 8-iso-PGF (2a), and products of the LOX-pathway [ 62 ]. Lastly, cigarette smoking, stimulating osteoclastic cells and reducing angiogenesis, impairs bone healing and tissues reparative response [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…We thank Dr Balto and Dr Al-Ekrish for their interest and constructive comments on the study in which we systematically reviewed the association between tobacco smoking and the prevalence of apical periodontitis and root canal treatment. In advance, we congratulate them for their study analysing the prevalence of apical periodontitis in smokers and nonsmokers using CBCT (Balto et al 2019).…”
Section: Dear Editormentioning
confidence: 99%